PM.07 A Prospective Study of Changes in Maternal Cardiovascular and Metabolic Function from Prior to Pregnancy to Postpartum. (26th April 2013) - Mahendru, AA; Everett, TR; McEniery, CM; Wilkinson, IB; Lees, CC
Abstract : Cardiovascular adaptation in normal pregnancy is the key to understanding cardiovascular function in pregnancy complications. The objective of this study was to investigate changes in maternal cardiovascular function during pregnancy, from a pre-pregnancy baseline to the postpartum period. In this prospective study, 54 women had normal pregnancy outcome; 5 had preeclampsia (PE) and/or intrauterine growth insufficiency (IUGR). Detailed haemodynamics were assessed pre-pregnancy, at median gestation of 6, 23 and 33 weeks and 16 weeks postpartum. Lipid profile and renal function were assessed pre-pregnancy, in first trimester and postpartum. While heart rate (HR) increased throughout pregnancy ( P = 0.001), brachial and central BP, together with peripheral vascular resistance (PVR) and wave reflections were reduced very early in pregnancy ( P < 0.001), followed by an increase in third trimester. Cardiac output (CO) increased to a peak by second trimester ( P = 0.001). The HR, CO and PVR returned to pre-pregnancy values in the postpartum period. However, the reduction in BP was sustained postpartum. The MAP increased in second trimester rather than a decrease in women with PE/IUGR ( P = 0.02). Lipids and creatinine decreased in first trimester ( P < 0.001). This is the first study to investigate longitudinal changes in central BP and wave reflections from pre-pregnancy to postpartum. We demonstrated profound changes in BP and arterial wave reflections very early in pregnancy; however CO peaks in the second trimester. The reduction in BP below pre-pregnancy values was sustained postpartum. Prospective studies of cardiovascular adaptation, beginning from pre-pregnancy are more likely to provide reliable estimates of pregnancy related maternal cardiovascular changes.